Historical dictionary of Heidegger's philosophy. - Schalow, Frank, 1956- (Historical dictionaries of religions, philosophies, and movements, 2010)
By the time Martin Heidegger passed away on May 26th, 1976, he had become the most important and controversial philosopher of his age. While many of his former students had become important philosophers and thinkers in their own right, Heidegger also inspired countless others, like Jacques Derrida, Michel Foucault, and Jean-Paul Sartre. The second edition of the Historical Dictionary of Heidegger's Philosophy is an historical perspective on the development of Heidegger's thought in all its nuancesand facets. Schalow and Denker cast light on the historical influences that shaped the thinker an.